A new compound arithmetic crossover-based genetic algorithm for constrained optimisation in enterprise systems - Jin Ch. Chenxia; Li F. Fachao; Tsang E. C. C. Eric; Bulysheva L. Larissa; Kataev M. Yu. Mikhail Yurievich (2015, 2015)
Title screen